Refractory in-stent stenosis after flow diverter stenting associated with delayed cobalt allergic reaction. (25th August 2021) - Fujii, Shoko; Fujita, Kyohei; Yamaoka, Hiroto; Miki, Kazunori; Hirai, Sakyo; Nemoto, Shigeru; Sumita, Kazutaka
Abstract : In-stent stenosis (ISS) triggered by a metal-induced allergic reaction of Pipeline embolization device (PED) placement is extremely rare. The present report describes a patient who presented with delayed parent artery occlusion and refractory ISS after PED placement due to cobalt allergy. A patient in her 70s underwent PED placement for a right internal carotid artery (ICA) large aneurysm; 4 months later, the patient presented with left-sided hemiparesis, and MRI revealed right ICA occlusion even though antiplatelet therapy was optimal. She underwent mechanical thrombectomy, and successful recanalization was achieved. However, follow-up angiography 6 months after the thrombectomy revealed severe ISS, and the patch testing showed a positive reaction for cobalt. As a result of long-term administration of oral steroids and antihistamine, progression of ISS was suppressed. It was supposed that a delayed hypersensitivity reaction to cobalt might induce refractory ISS after PED placement.